In Vitro Biomechanical Study of Femoral Neck Fracture Fixation with Two or Three Cannulated Screws in Dogs - Caldeira, Fátima Maria C. [UNESP]; Rahal, Sheila C. [UNESP]; Cassanego, Guilherme R. [UNESP]; Ribeiro, Celso R.; Serrato, Sergio A.A.; Mele, Carlos E.; Masseran, Paulo (Thieme, 2024)
Objective  To evaluate the in vitro mechanical properties of basilar fractures of the femoral neck stabilized with two or three titanium-cannulated screws in dogs. Study Design  Ex vivo study. Sample Population  Cadaveric canine femur (n = 21). Methods  The bones were divided as follows: Group 1: control (no osteotomy); Group 2: osteotomy and stabilization with two cannulated screws; and Group 3: osteotomy and stabilization with three cannulated screws. All groups were tested with destructive axial compression with load applied to the femoral head. The stiffness, load, and displacement were evaluated at the failure of Group 1, and the yield load and displacement of Groups 2 and 3. Results  The placement of the three cannulated screws was more demanding than two cannulated screws because of the risk of cortical perforation, especially in the trochanteric fossa area. The smaller the width of the femoral neck, the higher the risk of cortical bone wall perforation. The intact control bones were stiffer (674 N/mm) than both the two-screw repair (90 N/mm) and three-screw repair (120 N/mm) groups (p < 0.05). The failure load was greatest for Group 1 (2692 N). The yield loads for Groups 3 and 2 were 586 and 303 N, respectively. There was no difference between groups for displacement. Conclusion  In vitro cadaveric models of femoral neck basilar fractures repaired with three cannulated screws were significantly stronger than two cannulated screws, but the clinical efficacy must be evaluated by comparing them in vitro with noncannulated stainless steel screws.
Keywords: cannulated screws; femur; fracture; mechanical testing